Catheter-assisted 360-Degree Trabeculotomy for Congenital Glaucoma. Issue 7 (July 2018) - Toshev, Anani P.; Much, Martin M.; Klink, Thomas; Pfeiffer, Norbert; Hoffmann, Esther M.; Grehn, Franz
Abstract : Purpose: To determine feasibility, efficacy, and safety of ab externo 360-degree trabeculotomy with illuminated microcatheter for congenital glaucoma. Patients and Methods: The postoperative results of 36 eyes in 23 consecutive patients who underwent 360-degree trabeculotomy for primary congenital glaucoma (PCG) or secondary congenital glaucoma using an illuminated microcatheter were retrospectively analyzed. Success criteria were defined as intraocular pressure (IOP) ⩽18 mm Hg without (complete success) and with medication (qualified success). Results: In all previously nonoperated eyes with PCG (group 1), the Schlemm's canal was identified and circumferentially cannulated for 360-degree trabeculotomy. In group 2 comprising of operated eyes with PCG and eyes with secondary congenital glaucoma, the performance of 360-degree trabeculotomy failed in 4 eyes because of the Schlemm's canal occlusion or high tissue resistance of the trabecular meshwork. Mean preoperative IOP was 28.6±5 and 29.6±9 mm Hg with 7 of 20 eyes and 7 of 9 eyes receiving IOP-lowering medication in group 1 and group 2, respectively. Mean postoperative IOP was reduced to 13±2.7 and 20.2±7.1 mm Hg after a mean follow-up of 15.3 and 12.7 months with 4 of 20 eyes and 5 of 9 eyes receiving medication in group 1 and group 2, respectively. Four eyes underwent further surgery. Complete success was achieved in 16 and 3 eyes, whereas qualified success was achieved in 20 and 4 eyes from group 1 and group 2, respectively. In all eyes, a mild to moderate postoperative hyphema was observed. Conclusions: Ab externo catheter-assisted 360-degree trabeculotomy controls IOP in a majority of patients with congenital glaucoma after a single operation. Moderate blood reflux in the anterior chamber is considered as a common postoperative finding. We did not observe hypotony or other severe complications in our series. In 1 patient, we experienced catheter misdirection in an eye that had previously undergone trabeculotomy.